2010
DOI: 10.17221/75/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of wheat cultivars to bacterial inoculation in calcareous soil

Abstract: In this study the plant growth-promoting bacteria were analysed for their growth-stimulating effects on two wheat cultivars. The investigations were carried out in pot experiments using calcareous soil. The results showed that bacterial strains Pseudomonas spp. NUU1 and P. fluorescens NUU2 were able to colonize the rhizosphere of both wheat cultivars. Their plant growth-stimulating abilities were affected by wheat cultivars. The bacterial strains Pseudomonas sp. NUU1 and P. fluorescens NUU2 significantly stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…Furthermore, these weight increases were so profound in P. austalis with treatment PSOFM and in E. crassipes for all applied treatments, resulting in higher plants biomass in the treated contaminated soils than the uncontaminated control. Although, there is paucity of information regarding plant biomass enhancement under crude oil contamination, previous reports in uncontaminated soils lend credence to the findings here reported that soil solarization, inoculation of plant growth promoting rhizobacteria and fungi as well as NPK fertilization enhances plant biomass (Stapleton and De Vay, 1981;Jeon et al, 2003;Egamberdieva, 2010;Asaolu et al, 2012;Strasil, 2012;Rahman and Akter, 2012;Abbas et al, 2013).…”
Section: Time (Day) Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, these weight increases were so profound in P. austalis with treatment PSOFM and in E. crassipes for all applied treatments, resulting in higher plants biomass in the treated contaminated soils than the uncontaminated control. Although, there is paucity of information regarding plant biomass enhancement under crude oil contamination, previous reports in uncontaminated soils lend credence to the findings here reported that soil solarization, inoculation of plant growth promoting rhizobacteria and fungi as well as NPK fertilization enhances plant biomass (Stapleton and De Vay, 1981;Jeon et al, 2003;Egamberdieva, 2010;Asaolu et al, 2012;Strasil, 2012;Rahman and Akter, 2012;Abbas et al, 2013).…”
Section: Time (Day) Discussionsupporting
confidence: 79%
“…Ramteke et al (2013), studied effect of NPK fertilizer on root growth of three plants and reported that while fertilization stimulated the root growth of Vigna catjang it failed to do so with Pisum sativum and Vigna radiant. Similarly, Egamberdieva (2010), reported that while the inoculation of two species of Pseudomonas (Pseudomonas spp. NUU1 and P. fluorescens NUU2) stimulated the root growth of one of two cultivars of wheat (Turon) by 46.0 %, it failed to do so with the other wheat cultivar (Residence).…”
Section: Time (Day) Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sulfur deficiency symptom could easily be noted in maize plant, hence it is considered as indicator plant for assessing the sulfur deficiency of soils (Grayston and Germida, 1991). Inoculation experiments with microbes initially are performed under gnotobiotic condition in sand to assess their colonization potential (Egamberdieva, 2010). Hence, in the current study, plant growth promoting potential of thiosulfate oxidizing bacteria was assessed in sand under gnotobiotic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the plant growth promotion of wheat and maize were assessed through inoculation of Pseudomonas sp. and nitrogen fixers, respectively in sand under gnotobiotic condition (Mehnaz and Lazarovits, 2006;Egamberdieva, 2010). In the growth chamber study, sulfur is normally used instead of thiosulfate, as it is considered an effective fertilizer or soil acidulant in a wide range of agricultural soils (Janzen and Bettany, 1987).…”
Section: Discussionmentioning
confidence: 99%